Management of Buccal Screw Access Hole Positioning for Implant Fixed Complete Dentures: A Report of Two Patients and a Proposed Decision Tree - Fawaz Alzoubi (Case Reports in Dentistry)
The present report demonstrated the use of two methods to correct the positioning of buccal screw access holes in both implant- and abutment-level implant-supported fixed complete dentures in two patients. The report suggests that nonaxially tightened abutments (in this report, dynamic abutments), angled multi-unit abutments, and the use of a milled framework with individual crowns aid in masking buccal screw access holes while maintaining the benefits of a screw-retained design. A decision tree is also proposed to facilitate the workflow when faced with such clinical scenarios.